Oral communication strategies preferences in Arabic debate among non-Arabic speakers - Mohamed, Ahmad Syahmi; Mustapha, Nik Farhan; Mohamad, Ab Halim; Shamshudeen, Rosya Izyanie; Mohmad Rouyan, Nurazan (HRMARS, 2021)
Debate is a language learning activity that requires the debater to choose effective oral communication strategies to weaken the opponent. Thus, this study was conducted to identify the oral communication strategies preferences among Arabic language debaters consisting of non-native speakers. The respondents were the champions of the Higher Education Institutions level debate, while the data were obtained from video recordings of the debate competition and interviews. The data were then analysed using Communication Strategies Theory. The results showed that the debaters preferred the strategies of message abandonment, topic avoidance and appeal for assistance when short of time and approximation and word coinage when faced with language constraints. Literal and contextual translation and language switch strategies were chosen for debate preparations, while circumlocution and mime strategies were preferred for reinforcing arguments. A new strategy was also found, which is named as repetition strategy. The findings proved that the preference of these strategies help the debaters to organize ideas, articulate and confidently present arguments despite their own shortcomings and interruptions from opponents. This study contributes to the structure of debate training activities focused on more systematic oral communication strategies that can be applied to debaters in Arabic language learning classes.